GDI spray structure analysis by polycapillary X-ray μ-tomography. (April 2015) - Marchitto, L.; Hampai, D.; Dabagov, S.B.; Allocca, L.; Alfuso, S.; Polese, C.; Liedl, A.
Highlights: 3D X-ray tomography has been applied to investigate the structure of gasoline spray. A portable X-ray source has been used instead of a synchrotron radiation source. Quantitative measurements of fuel mass density have been performed. The effect of interaction between the jets on the density distribution is highlighted. Abstract: A X-ray μ -tomography technique, using a Cu K α source at 8.048 keV coupled with both polycapillary optics and CCD detector, has been developed to reconstruct the composition of a transient gasoline spray generated by a high-pressure GDI injector for automotive applications. The polycapillary elements enable shaping the divergent beams and getting high-contrast images due to the suppression of radiation multiple scattering. A pressure-tight device permits the 360 ° rotation of a six-hole nozzle, with a step of 0.1 °, at injection pressures up to 20 MPa, while the spray plume develops in a vented Plexiglas chamber at the atmospheric backpressure. The entire system is configured as a table-top experiment. The extinction images acquired along the X-ray source-spray-detector line-of-sight have permitted the reconstruction of a 3D structure together with a morphology of the jets within a 3 mm region downstream the nozzle. The spray shape as well as the propagation direction can be clearly identified in the tomographic reconstruction for all the six jets. Quantitative measurements of the fuel mass density in the near nozzle region have been performed. Typical Gaussian-shape distribution of the intensities appears for the cross sections revealing the more dense jet regions in the core, while slight longitudinal asymmetries indicate an interaction between the jet plumes.